Implications of intracochlear decomposition gas formation in non-putrefied cadavers - Mittmann, Philipp; Ernst, Arne; Seidl, Rainer; Lauer, Gina; Gölz, Leonie; Mutze, Sven; Windgassen, Marc; Buschmann, Claas (Frontiers in Surgery, 2024)
Postmortem computed tomography (pmCT) prior to forensic autopsy has become increasingly important in recent decades, especially in forensic documentation of single injuries, injury patterns. and causes of death. Postmortem decomposition gas formation can also be detected in pmCT scans which might affect cochlear implant research in postmortem human temporal bones.Material and Methods 50 non-putrefied hanging fatalities from a two year-period (January 2017 to March 2019) were included with 100 temporal bones (TB). Each body underwent whole-body-pmCT prior to forensic autopsy. PmCT scans were analyzed with respect to presence of intracochlear gas despite lack of putrefaction at autopsy by an experienced fellow neurootologist.PmCT revealed gas formation in two individuals despite lack of head trauma and putrefaction at postmortem examination and autopsy. Both individuals showed enclosed gas in the vestibule and the cochlea on both sides.Intracochlear gas formation, most likely related to decomposition, may occur despite lack of putrefaction at postmortem examination and autopsy and can be detected by pmCT. This finding seems to be rather rare in non-traumatic death cases but might affect cochlear pressure research in postmortem human TB.